2021
DOI: 10.1186/s13006-021-00365-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal experience of intimate partner violence is associated with suboptimal breastfeeding practices in Malawi, Tanzania, and Zambia: insights from a DHS analysis

Abstract: Background Despite widespread suboptimal breastfeeding practices and maternal experiences of intimate partner violence (IPV), the association of IPV and breastfeeding practices remains unclear. This study investigated the associations between maternal experience of physical, sexual, emotional violence, and controlling behaviors with suboptimal breastfeeding practices in Malawi, Tanzania, and Zambia. Methods Data included mother-infant dyads from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 25 publications
0
13
0
14
Order By: Relevance
“…The results did not observe differences in exclusive breastfeeding duration in mothers exposed or not to any kind of violence. 17 Also, studies in Zambia, Malawi e Tanzania; Bangladesh; Africa (including eight countries), Nigeria and India 8,18,19 presented diverging results. All of these studies used, as a data source, the Demographic and Health Survey to estimate the effect of domestic violence against women during pregnancy on breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results did not observe differences in exclusive breastfeeding duration in mothers exposed or not to any kind of violence. 17 Also, studies in Zambia, Malawi e Tanzania; Bangladesh; Africa (including eight countries), Nigeria and India 8,18,19 presented diverging results. All of these studies used, as a data source, the Demographic and Health Survey to estimate the effect of domestic violence against women during pregnancy on breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…18 The study in Zambia, Malawi and Tanzania showed that maternal experience of various types of IPV was associated with suboptimal breastfeeding practices in all three countries. 8 A study conducted in eight African countries (Ghana, Kenya, Liberia, Malawi, Nigeria, Tanzania and Zambia) showed that violence by an intimate partner had a tendency to be associated with suboptimal breastfeeding practices, and sexual violence was more frequently associated with inappropriate breastfeeding practices. 22 Finally, the study conducted in Nigeria found that the experience of intimate partner violence is also related to improper practices of exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers from Malawi (n=1,878), Tanzania (n=3,184), and Zambia (n=3,879) participated in Demographic and Health Surveys to examine the link between IPV and breastfeeding outcomes 25 . The rates of breastfeeding initiation the first hour after birth and exclusive breastfeeding were high in all three countries.…”
Section: Intimate Partner Violence and Breastfeedingmentioning
confidence: 99%
“…Further, IPV survivors experiencing poor mental and physical health are more likely to be less productive, thus reducing their contributions to societal development [ 3 , 5 ]. In addition, studies have linked IPV to poor sexual and reproductive health (SRH) and child health outcomes, including HIV, unintended pregnancies, pregnancy loss, suboptimal breastfeeding, and infant and child mortality [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%